What Did Latino Family Caregivers Expect and Learn From Education Intervention "Caregivers Like Me"?. (March 2018) - Cruz-Oliver, Dulce M.; Parikh, Manas; Wallace, Cara L.; Malmstrom, Theodore K.; Sanchez-Reilly, Sandra
Objective: US Latinos historically have underutilized end-of-life (EOL) resources. This study reports the views of family caregivers before and after education intervention Caregivers Like Me geared to improve knowledge and attitudes regarding EOL resources among Latino caregivers. Methods: This is a qualitative substudy within a multicentered cross-sectional study design. Educational intervention was offered to family caregivers of Latino elders from 3 different communities, using an audiovisual presentation, including a case-based video telenovela and pre–posttest questionnaires with open-ended questions. This study pertains to the qualitative results for the open-ended questions before and after education intervention. Results: Participants (N = 145) were mostly females (79%) with a mean age of 56 ± 15 years and reported (92%) active learning from intervention. The pretest open-ended question on expected learning identified 2 themes, care for the sick and self-care . It included 5 subthemes and the most common one was how to help the sick . The posttest question on actual learning identified the same 2 themes and 4 subthemes that were similar but different from the pretest. Accepting help and knowledge of services available were the most common. Conclusion: The education intervention Caregivers Like Me was able to improve attitudes toward EOL care because participants who wanted to help their loved ones realized that they need to accept professional help and were made aware of the services available.